Goodyera nanshanensis (Orchidaceae, Orchidoideae, Cranichideae, Goodyerinae), a new species from Hunan, China - Wang, Xi-Long; Chen, Juan; Jin, Xiao-Hua (Phytotaxa, 2020)
Goodyera nanshanensis, a new species from Hunan Province, China, is described and illustrated. Goodyera nanshanensis is morphologically similar to Goodyera recurva, but differs from it by having leaves with irregular transverse white markings, lateral sepals connate about one fifth at base, and lip 2.5 mm long.